Диантипирилметановые комплексы циркония и их применение в анализе - Штокало, Мирослава Иосифовна; Островская, Мира Семеновна; Рыженко, Виктория Леонидовна; Перепеченко, Е. Е. (My University, 1979)
Установлены оптимальные условия комплексообразования состав комплекса, рассчитана константа устойчивости. Предложена схема взаимодействия в системе. Разработана методика определения металла. The optimum conditions of the reaction and the composition of complex that is formed were found. The complexformation constant were calculated. The Offered scheme of the interaction in system. The methods of the determination of the metal is designed.
Keywords: фотометрия; комплексообразование; определение металлов; complexation; definition the metal; photometry; кафедра харчової хімії